Macroinvertebrate Diversity as Bioindicator of Water Quality in Anggoeya River, Kendari City - Koty, Agnes Trixsy; Kahirun, Kahirun; Bana, Sahindomi; Sudia, La Baco; -, La Ode Muhammad Erif (Journal of Soilscape and Agriculture, 2024)
Anthropogenic activities will affect the quality of river water and the living things in it, including macroinvertebrates. Anggoeya River is one of the rivers that water source is used as raw water for PDAM Kendari, so its quality needs to be considered. The purpose of this study was to analyze the water quality of Anggoeya River using macroinvertebrate bioindicators and the relationship between macroinvertebrates and physicochemical parameters of water and substrate of Anggoeya River. Physico-chemical parameters consist of temperature, current velocity, TSS, turbidity, pH, COD, BOD, DO, substrate pH, and substrate type. The sampling technique used purposive sampling, where macroinvertebrate sampling was carried out at three points at each station three times repetitions, namely on the left, middle, and right sides of the river, based on the type of river habitat, namely pool, riffle, and rapid. Top of Form The results obtained for the highest diversity value is at Station I with a value of 1.99 and the highest dominance value is at Station III with a value of 0.98. As for the best FBI value of the three stations, namely at Station II with a value of 5.43 with a moderate organic matter pollution category. For the results of physicochemical parameters, some of which do not meet or exceed the Quality Standards based on Government Regulation Number 22 of 2021, namely TSS at Station III, BOD at Station I and Station II, and DO at Station III. The results of the macroinvertebrate diversity index relationship with physicochemical parameters has a strong to very strong relationship.